2022
DOI: 10.1002/hpm.3547
|View full text |Cite
|
Sign up to set email alerts
|

Distance and health facility choice: Evidence from a health micro insurance program in Punjab, Pakistan

Abstract: Health micro insurance offers a promising mechanism to protect the poor against risk and vulnerability arising from catastrophic healthcare expenditures. In light of this, we study the relationship between physical distance to hospitals and the choice of healthcare services in the context of a health micro insurance program in Punjab, Pakistan. We address three main research questions; first, how does physical distance affect choice of health facility? Second, is the burden of physical distance greater for wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Given the high transportation costs coupled with poor road infrastructure, spending a longer time to reach health facilities might have led to dissatisfaction among the insured. Studies have shown that people would prefer private health facilities with no insurance service despite their high cost rather than traveling longer distances [43][44][45][46]. Similar to this finding, a study conducted in Nigeria revealed physical accessibility to health facilities as an important factor leading to higher user satisfaction [47].…”
Section: Plos Onementioning
confidence: 56%
“…Given the high transportation costs coupled with poor road infrastructure, spending a longer time to reach health facilities might have led to dissatisfaction among the insured. Studies have shown that people would prefer private health facilities with no insurance service despite their high cost rather than traveling longer distances [43][44][45][46]. Similar to this finding, a study conducted in Nigeria revealed physical accessibility to health facilities as an important factor leading to higher user satisfaction [47].…”
Section: Plos Onementioning
confidence: 56%